Eros e pulsione di morte: una libido, due regimi - Dalto, Silvana (Metapsychologica - rivista di psicanalisi freudiana, 2022)
In the years between 1920 and 1924 Freud is engaged in a significant improvement of metapsychology, conceived as a physics of the subject. Freud is dealing with a redefinition of the economic principles that govern psychic dynamics and with an extension of drive theory; he also proposes a new theory on the problem of pleasure, the development of which also has important consequences at an ethical level. These new theoretical achievements shed new light on the purposes of treatment, which are based on acknowledgment and not on therapy. The question of castration as an outlet of analysis is also rearticulated.